Effects of Lactobacillus rhamnosus ATCC 7469 on Different Parameters Related to Health Status of Rainbow Trout (Oncorhynchus mykiss) and the Protection Against Yersinia ruckeri - Hooshyar, Yalda; Abedian Kenari, Abdolmohammad; Paknejad, Hamed; Gandomi, Hassan (Probiotics and antimicrobial proteins, 2020)
In the current study, we investigated the effect of a probiotic bacterium ( Lactobacillus rhamnosus ATCC 7469) microencapsulated with alginate and hi-maize starch and coated with chitosan on improving growth factors, body composition, blood chemistry, and the immune response of rainbow trout (initial weight: 18.41 ± 0.32 g). Four experimental diets were formulated to feed fish for 60 days. They were control diet without any additive (C), diet added with beads without probiotic (E), a probiotic sprayed to the diet (L.r), and encapsulated probiotic supplemented diet (E-L.r). The results indicated that feeding with E-Lr significantly improved weight gain (84.98 g) and feed conversion ratio (0.95) compared to the other groups ( P < 0.05). Also, fish fed E-Lr diet had a significantly higher value of whole-body protein (17.51%), total protein in the blood (4.98 g/dL), lysozyme (30.66 U/mL), alternative complement pathway hemolytic activity (134 U/mL), superoxide dismutase (203 U/mg protein), and catalase (528.33 U/mg protein) ( P < 0.05) as compared to those fed the control diet. Similarly, a higher relative expression of immune-related genes such as interleukin-1 (Il-1) and tumor necrosis factor-alpha (TNF-1α) were reported in those fed E-L.r and L.r diets respectively. Interestingly, the fish fed dietary E-L.r had a significantly lower value of lipid in the whole body (4.82%) and cholesterol in the blood (160.67%) in comparison with those fed the control diet ( P < 0.05). At the end of the experiment, all groups were challenged by Yersinia ruckeri where the survival rate of rainbow trout fed dietary E-L.r (70.36%) was statistically higher than that of the others ( P < 0.05). Overall, the results suggested that encapsulated probiotic Lact . rhamnosus ATCC 7469 acted better than unencapsulated probiotic and has a potential to improve growth performance, flesh quality, and the immune response of rainbow trout.